Analysis of the Implementation of the Coretax System and Account Representative (AR) Services in Improving Individual Taxpayer Compliance at KPP Pratama Subang - Andini Indriyani; Usman Sastradipraja (Danadyaksa: Post Modern Economy Journal, 2026)
This research is motivated by efforts to modernize tax administration through the implementation of the Coretax system as a digital-based tax service that is expected to improve the quality of service and taxpayer compliance. However, in its implementation, various obstacles still exist that affect the system's effectiveness. The phenomenon found at KPP Pratama Subang shows that many taxpayers still experience difficulties when using the Coretax system, including frequent login failures, system errors, delays in taxpayer data verification, and confusion in understanding the features and procedures within the system. In addition, around 300–400 taxpayers per day visited KPP Pratama Subang to seek consultation and technical assistance regarding the use of Coretax, indicating that taxpayers’ understanding and adaptation to the new digital tax system are still relatively low. This condition demonstrates that the implementation of the Coretax system has not yet fully supported taxpayer convenience and compliance, and the role of Account Representatives (AR) is still highly needed in providing guidance, supervision, and assistance to taxpayers. This study aims to analyze the implementation of Coretax and the role of Account Representatives (AR) in improving individual taxpayer compliance at the Subang Pratama Tax Office (KPP Pratama). This study uses a qualitative approach with an exploratory method. Data were collected through interviews, observations, and documentation with informants consisting of individual taxpayers, Account Representatives (AR), and tax counselors. Data analysis was conducted using a comparative technique using a percentage approach. The results show that the implementation of Coretax is still suboptimal (31.25%) due to technical constraints, access, and taxpayer understanding. The role of Account Representatives (AR) is also not optimal (43.75%), especially in the aspects of communication and guidance. Meanwhile, the level of taxpayer compliance is in the fairly good category (68.75%). Overall, it shows that the implementation of the Coretax system and Account Representative (AR) services in improving taxpayer compliance has not been running optimally.